Analysis of Factors Affecting the Stress Level of Female Engineering Students (Global Journal of Human-Social Science, 2012)
This paper presents factors that affect the stress level of female engineering students The questionnaire is based on the expectations which the female students have of their institutions as well as from their families Randomly collected data from 200 students is analyzed on software MINITAB 14 Six sigma techniques of Affinity diagram Pareto Analysis SIPOC analysis Cause and Effect matrix and Scatter plots are used It is observed that teachers discouraging attitude to take females on industrial trips and lack of class tests during the academic session are the most critical factors This work can guide the teachers as well as the educational leaders to precisely focus their resources for minimizing stress among female engineering students
Keywords: Stress factors; female engineering students; class tests; industrial trips; and sixsigma